KEGIATAN FIELDSTUDY DALAM PEMBENTUKAN KOMPETENSI PROFESIONAL CALON GURU GEOGRAFI - Munandar, Aris (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2019)
AbstractThe purpose of this study is to measure the formation of professional competencies in field study activities. The research was conducted on students who conducted field studies with the names PKL (Field Lecture Practices) at UNJ and KKL (Field Work Lectures) at UPI. There were 120 samples from 580 participants with sample quota with each of 20 students from 6 groups — measurement of professional competence by using multiple choice questions, 30 questions. Questions were constructed from the courses taken by participants in semesters 2, 4 and 6. The test results showed an average value of 56.84 with the lowest score of 44 and the highest of 77. The test results showed more in the medium category; there were no lows and fewer with the high category. The researcher concludes that professional competence in mastering the material has a low relationship. Professional competence in the form of knowledge is formed from other activities such as teaching in the classroom.Keywords: Field study, competence, professionalsAbstrakTujuan dari penelitian ini untuk mengukur pembentukan kompetensi professional dalam kegiatan fieldstudy. Penelitian dilakukan terhadap mahasiswa yang melakukan fieldstudy dengan nama PKL (Praktek Kuliah Lapangan) di UNJ dan KKL (Kuliah Kerja Lapangan) di UPI. Jumlah sampel 120 dari 580 peserta dengan kuota sampel dengan masing-masing 20 mahasiswa dari 6 kelompok. Pengukuran kompetensi profesional dengan meggunakan instrument soal pilihan ganda, 30 soal. Soal dikontruksi dari matakuliah yang sudah diambil peserta di semester 2, 4 dan 6. Hasil tes menunjukan nilai rata-rata 56,84 dengan nilai terendah 44 dan tertinggi 77. Hasil tes menunjukan lebih banyak pada kategori sedang, tidak ada yang rendah dan sedikit dengan kategori tinggi. Peneliti berkesimpulan kompetensi profesional penguasaan materi memiliki hubungan yang rendah. Kompetensi profesional berupa pengetahuan terbentuk dari kegiatan lain seperti pengajaran dikelas. Kata kunci : Fieldstudy, kompetensi, profesional